Current Knowledge Regarding Long-Term Consequences of Pediatric Intensive Care: A Staff Survey in Intensive Care Units in German-Speaking Countries - Von Borell, Florian; Engel, Juliane; Neunhoeffer, Felix; Hoffmann, Florian; Michel, Jörg (Frontiers in Pediatrics, 2022)
Background The Post Intensive Care Syndrome (PICS) describes new impairments of physical, cognitive, social, or mental health after critical illness. In recent years, prevention and therapy concepts have been developed. However, it is unclear whether and to what extent these concepts are known and implemented in hospitals in German-speaking countries. Methods We conducted an anonymous online survey in German-speaking pediatric intensive care units on the current state of knowledge about the long-term consequences of intensive care treatment as well as about already established prevention and therapy measures. The request to participate in the survey was sent to the heads of the PICUs of 98 hospitals. Results We received 98 responses, 54% of the responses came from nurses, 43% from physicians and 3% from psychologist, all working in intensive care. As a main finding, our survey showed that for only 31% of the respondents PICS has an importance in their daily clinical practice. On average, respondents estimated that about 42% of children receiving intensive care were affected by long-term consequences after intensive care. The existence of a follow-up outpatient clinic was mentioned by 14% of the respondents. Frequent reported barriers to providing follow-up clinics were lack of time and staff. Most frequent mentioned core outcome parameters were normal developmental trajectory (59%) and good quality of life (52%). Conclusion Overall, the concept of PICS seems to be underrepresented in German-speaking pediatric intensive care units. It is crucial to expand knowledge on long-term complications after pediatric critical care and to strive for further research through follow-up programs and therewith ultimately improve long-term outcomes.